Influence of Pre-Stressing on Tieback Retaining Wall for Sandy Soils Excavations - Anthonius Steven Sutanto; Paulus Pramono Rahardjo; Aswin Lim (Journal of the Civil Engineering Forum, 2021)
Pre-stressed ground anchor systems or tieback systems are commonly used at wide and irregular-shaped excavations, with the advantage of lower cost and ease of construction compared to the braced excavations, but they come with the drawback on permits for excavations near buildings and tunnels. Research on tieback systems in sands was generally conducted. However, the studies on the correlation between the retaining wall deflection and pre-stress force are few. The objectives of this paper are to study the influence of pre-stress force, depth of excavation, wall embedment length, and soil shear strength that is represented by soil friction angle on the deflection and soil pressure acting on the retaining wall. The parametric study was conducted on an excavation in sand using the finite element method with the Hardening soil model. The results showed that a 50 kN/m increase in pre-stress force reduced the wall deflection on top of the wall by 0.005–0.083% of excavation depth. However, the pre-stressing influence in reducing wall deflection at excavations became less significant along with the sand density increase due to higher friction angle contribution to excavation stability. Moreover, the pre-stress force needed for stabilization of the wall with long embedment length is smaller than those on the wall with shorter embedment length, since the embedment length increase of 0.25 times of excavation depth reduces wall top deflection by 0.002–0.095% of excavation depth. Also, the increase of soil density reduces the need for wall embedment length, so at dense sand, the embedment length of 0.5 times of excavation depth is sufficient to support the excavation.